Remote-sensing technology in mapping socio-economic divergence of Europe - Mikhaylov Andrey; Mikhaylova Anna; Alsynbaev Kamil; Bryksin Vitaliy; Hvaley Dmitry (Bulletin of Geography. Socio-Economic Series, 2021)
Marine and ocean coasts traditionally act as natural growth poles for humankind. Recent studies conducted by scholars from both natural and social sciences suggest that coastal zones accumulate population, agglomerate industries, attract entrepreneurs, and pull investments. The coastalisation effect remains one of the defining factors of regional development around the globe and is projected to strengthen over the next quarter century. Deepening socio-economic inequality and polarisation between countries and regions despite efforts taken with convergence policies put the “marine factor” on the research agenda. The study contains a comparative evaluation of coastalisation processes across the regions of Europe using remote-sensing technology and statistical multivariate analysis for testing the correlation level of results. The research is based on a dataset for 413 regions of Europe featuring indicators for population density and Gross Regional Product (GRP) in Purchasing Power Parity (PPP) per sq. km. The regions are grouped into clusters depending on their socio-economic indicators and the intensity of nocturnal illumination. The results suggest that coastal and inland region types evenly distribute between clusters, with an average of 40% coastal. Observations of nocturnal illumination clearly indicate an extensive anthropogenic impact on European coasts, both northern and southern. However, their overall luminosity is inferior to inland territories. The study concludes with four patterns derived from a combined methodology of socio-economic indicators and remote-sensing of night-time lighting.